Positive electrode material and preparation method thereof, positive plate, lithium ion battery and electric equipment
By covering the manganese phosphate layer on the surface of the ternary positive electrode material, the problems of ion mixing and side reactions of traditional materials during circulation are solved, and the ratio and circulation performance are improved, and safety is improved.
Patent Information
- Application Number
- CN202411502844.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-25
- Publication Date
- 2024-12-17
AI Technical Summary
Traditional high-nickel ternary cathode materials have ion mixing, lattice distortion and side reactions during the circulation process, resulting in poor rate performance and cycle performance.
The manganese phosphate layer is coated on the surface of the ternary positive electrode material by co-precipitation method, and oxygen ions are suppressed through the P-O bond of the phosphate, interface stability is improved, electrolyte is isolated, and crystal structure is stabilized.
It improves the chemical stability and rate performance of the positive electrode material, enhances the circulation performance, reduces the occurrence of side reactions, and improves safety.
Smart Images

Figure CN119153665A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of lithium-ion batteries, and particularly to a cathode material, a preparation method thereof, a cathode sheet, a lithium-ion battery, and an electrical device using the same. Background Art
[0002] Secondary batteries represented by lithium-ion batteries have advantages such as high working voltage, high energy density, good safety, and no memory effect, and have achieved great success in fields such as portable electronic devices, electric vehicles, and hybrid electric vehicles. Currently, among traditional secondary batteries, ternary materials are widely used due to advantages such as high capacity and energy density. However, the current ternary materials still have problems of poor cycling performance and rate performance. Summary of the Invention
[0003] Based on this, the present application provides a cathode material, a preparation method thereof, a cathode sheet, a lithium-ion battery, and an electrical device using the same, which can improve the cycling performance and rate performance of the battery.
[0004] The first aspect of the present application provides a cathode material, including: a core and a coating layer covering at least a part of the surface of the core, the core containing a ternary cathode material, the ternary cathode material satisfying the chemical formula LiNi x Co y Mn 1-x- y O2, 0.6 ≤ x < 1, 0 < y ≤ 0.1, and the coating layer contains manganese phosphate.
[0005] In some embodiments of the present application, one or more of the following conditions are satisfied:
[0006] (1) The mass ratio of the coating layer in the cathode material is 1% - 5%, and can be 2% - 4%;
[0007] (2) The thickness of the coating layer is less than 10 nm;
[0008] (3) The content of phosphorus element in the cathode material is 1500 ppm - 9000 ppm, and can be 3800 ppm - 5000 ppm.
[0009] In some embodiments of the present application, the layer spacing of the ternary cathode material is 0.47 nm - 0.48 nm.
[0010] The second aspect of the present application provides a preparation method of a cathode material, including:
[0011] Adding a second solution containing a source of dihydrogen phosphate to a first solution containing a ternary cathode material matrix and a manganese source, and preparing a precursor for coating after reaction;
[0012] The coated precursor is calcined to prepare the cathode material, which includes a core and a coating layer covering at least a part of the surface of the core. The core contains a ternary cathode material, and the ternary cathode material satisfies the chemical formula LiNi x Co y Mn 1-x-y O2, where 0.6 ≤ x < 1 and 0 < y ≤ 0.1, and the coating layer contains manganese phosphate.
[0013] In some embodiments of the present application, one or more of the following conditions are satisfied:
[0014] (1) In the first solution, the mass ratio of the manganese source to the ternary cathode material matrix is (1.5 - 5):100;
[0015] (2) In the first solution, the mass ratio of the ternary cathode material matrix to the solvent is (0.1 - 3):1;
[0016] (3) The mass ratio of the dihydrogen phosphate source to the manganese source is (45 - 50):100;
[0017] (4) In the second solution, the mass ratio of the dihydrogen phosphate source to the solvent is (0.077 - 0.385):1;
[0018] (5) The manganese source includes one or more of manganese sulfate, manganese acetate, and manganese chloride;
[0019] (6) The dihydrogen phosphate source includes one or more of ammonium dihydrogen phosphate, sodium dihydrogen phosphate, lithium dihydrogen phosphate, and potassium dihydrogen phosphate.
[0020] In some embodiments of the present application, adding a second solution containing a dihydrogen phosphate source to a first solution containing a ternary cathode material matrix and a manganese source includes:
[0021] Under stirring conditions, the second solution is added dropwise to the first solution;
[0022] Optionally, the dropping rate is 2.5 mL / h - 10 mL / h.
[0023] In some embodiments of the present application, one or more of the following conditions are satisfied:
[0024] (1) The temperature of the calcination treatment is 250°C - 350°C;
[0025] (2) The time of the calcination treatment is 5 h - 6 h;
[0026] (3) The atmosphere of the calcination treatment includes an oxygen atmosphere and / or an air atmosphere.
[0027] The third aspect of the present application provides a positive electrode sheet, comprising the positive electrode material of the first aspect of the present application or the positive electrode material prepared by the preparation method of the second aspect of the present application.
[0028] The fourth aspect of the present application provides a lithium-ion battery, comprising the positive electrode sheet of the third aspect of the present application.
[0029] A fifth aspect of the present application provides an electrical device comprising the lithium-ion battery of the fourth aspect.
[0030] The electrical equipment of the present application includes the lithium-ion battery provided by the present application, and thus has at least the same advantages as the lithium-ion battery.
[0031] The positive electrode material provided in the present application includes a core and a coating layer, and the nickel content of the ternary positive electrode material contained in the core is relatively high. By coating the surface of the high-nickel ternary positive electrode material with a coating layer containing manganese phosphate, on the one hand, the PO bond with a stronger bond strength in the phosphate group can be used to prevent the release of oxygen ions in the crystal skeleton of the ternary positive electrode material, inhibit the collapse of the structure of the positive electrode material itself, and improve its chemical stability, thereby facilitating the improvement of its rate performance. On the other hand, the coating layer can isolate the positive electrode material from the electrolyte, thereby improving the interfacial stability of the positive electrode material, inhibiting its side reactions, and stabilizing the crystal structure of the ternary positive electrode material, thereby facilitating the improvement of the cycle performance of the positive electrode material. BRIEF DESCRIPTION OF THE DRAWINGS
[0032] FIG. 1 is an energy spectrum scanning analysis (EDS-mapping) diagram of the positive electrode materials of Comparative Example 1 and Example 3, wherein FIG. 1 (a) is the EDS-mapping diagram of Comparative Example 1, and FIG. 1 (b) is the EDS-mapping diagram of Example 3.
[0033] FIG2 is a scanning electron microscope image of the positive electrode material of Comparative Example 1, wherein FIG2(a) is a scanning electron microscope image at a magnification of 5K, and FIG2(b) is a scanning electron microscope image at a magnification of 20K.
[0034] FIG3 is a scanning electron microscope image of the positive electrode material of Example 1, wherein FIG3(a) is a scanning electron microscope image at a magnification of 5K, and FIG3(b) is a scanning electron microscope image at a magnification of 20K.
[0035] FIG4 is a scanning electron microscope image of the positive electrode material of Example 2, wherein FIG4(a) is a scanning electron microscope image at a magnification of 5K, and FIG4(b) is a scanning electron microscope image at a magnification of 20K.
[0036] FIG5 is a scanning electron microscope image of the positive electrode material of Example 3, wherein FIG5(a) is a scanning electron microscope image at a magnification of 5K, and FIG5(b) is a scanning electron microscope image at a magnification of 20K.
[0037] FIG6 is a scanning electron microscope image of the positive electrode material of Example 4, wherein FIG6(a) is a scanning electron microscope image at a magnification of 5K, and FIG6(b) is a scanning electron microscope image at a magnification of 20K.
[0038] FIG. 7 is a transmission electron microscope image of the positive electrode materials of Comparative Example 1 and Example 3, wherein FIG. 7 (a) is a transmission electron microscope image of Comparative Example 1, and FIG. 7 (b) is a transmission electron microscope image of Example 3.
[0039] FIG8 is an X-ray diffraction analysis diagram of the NCM powder sample, coated precursor and positive electrode material of Example 4.
[0040] FIG9 is a partial enlarged X-ray diffraction diagram of the NCM powder sample, coated precursor and positive electrode material of Example 4.
[0041] FIG10 is an X-ray diffraction analysis diagram of the positive electrode materials of Examples 1 to 4 and Comparative Example 1. DETAILED DESCRIPTION
[0042] In order to facilitate understanding of the present application, the present application will be described more comprehensively below. However, the present application can be implemented in many different forms and is not limited to the embodiments described herein. On the contrary, the purpose of providing these embodiments is to make the understanding of the disclosure of the present application more thorough and comprehensive.
[0043] For simplicity, this application only explicitly discloses some numerical ranges. However, any lower limit can be combined with any upper limit to form an unclearly recorded range; and any lower limit can be combined with other lower limits to form an unclearly recorded range, and any upper limit can be combined with any other upper limit to form an unclearly recorded range. In addition, although not clearly recorded, each point or single value between the range endpoints is included in the range. Thus, each point or single value can be combined with any other point or single value as its own lower limit or upper limit or with other lower limits or upper limits to form an unclearly recorded range.
[0044] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those generally understood by those skilled in the art to which this application belongs. The terms used herein in the specification of this application are for the purpose of describing specific embodiments only and are not intended to limit this application. It should be noted that, unless otherwise specified, the term "and / or" used herein includes any and all combinations of one or more related listed items, and "above" and "below" are inclusive of the number, and the meaning of "multiple" in "one or more" is more than two.
[0045] Herein, when it comes to a numerical interval (i.e., a numerical range), unless otherwise specified, the distribution of the optional numerical values within the numerical interval is considered to be continuous and includes the two numerical endpoints (i.e., the minimum and maximum values) of the numerical interval, and each numerical value between the two numerical endpoints. Unless otherwise specified, when a numerical interval only refers to integers within the numerical interval, including the two endpoint integers of the numerical range, and each integer between the two endpoints, is equivalent to directly listing each integer. When multiple numerical ranges are provided to describe features or characteristics, these numerical ranges can be combined. In other words, unless otherwise specified, the numerical ranges disclosed herein should be understood to include any and all sub-ranges included therein. The "numerical value" in the numerical interval can be any quantitative value, such as a number, a percentage, a ratio, etc. "Numerical interval" allows broadly including numerical interval types such as percentage intervals, ratio intervals, and ratio intervals.
[0046] In this article, if there are multiple steps involved in the method flow, unless there is a clear different description in this article, there is no strict order restriction for the execution of these steps, and they can be executed in other orders than described. Moreover, any step can include multiple sub-steps or multiple stages, and these sub-steps or stages are not necessarily executed at the same time, but can be executed at different times, and their execution order is not necessarily sequential, but can be executed in turn, alternating or simultaneously with other steps or parts of sub-steps or stages of other steps.
[0047] The above application content of the present application is not intended to describe each disclosed embodiment or each implementation in the present application. The following description more specifically illustrates exemplary embodiments. In many places throughout the application, guidance is provided by a series of examples, which can be used in various combinations. In each example, enumeration is only used as a representative group and should not be interpreted as exhaustive.
[0048] During the research, the inventors found that due to the high nickel content, the traditional high-nickel ternary positive electrode material will produce a large degree of ion mixing during the cycle, which will hinder the ion transmission channel and lead to a decrease in rate performance. At the same time, ion mixing will also be accompanied by severe lattice distortion. During the charge and discharge process, large stress will be generated inside the material particles, forming microcracks, reducing the mechanical stability of the material particles and aggravating the degree of interface side reactions, resulting in poor cycle performance. In order to solve the above-mentioned technical problem, the inventors proposed the following technical solution of this application.
[0049] In a first aspect, the present application provides a positive electrode material, comprising: a core and a coating layer covering at least a portion of the surface of the core, wherein the core comprises a ternary positive electrode material, and the ternary positive electrode material satisfies the chemical formula LiNi x Co y Mn1-x- y O2, where 0.6 ≤ x < 1 and 0 < y ≤ 0.1, and the coating layer contains manganese phosphate.
[0050] The cathode material provided by this application includes a core and a coating layer. The ternary cathode material in the core has a relatively high nickel content. By coating a coating layer containing manganese phosphate on the surface of this high-nickel ternary cathode material, on the one hand, the relatively strong P-O bond in the phosphate group can be used to prevent the release of oxygen ions in the crystal skeleton of the ternary cathode material, inhibit the collapse of the structure of the cathode material itself, and improve its chemical stability, thus facilitating the improvement of its rate performance.
[0051] On the other hand, the coating layer can isolate the cathode material from the electrolyte, thereby improving the interfacial stability of the cathode material, inhibiting its side reactions, and stabilizing the crystal structure of the ternary cathode material, thus facilitating the improvement of the cycle performance of the cathode material. In addition, the manganese element in manganese phosphate has relatively low electrochemical activity and is not easily involved in the redox reaction during the cycle, which is beneficial to stabilizing the layered structure of the ternary cathode material and improving its safety.
[0052] In some embodiments, the ternary cathode material includes LiNi 0.96 Co 0.03 Mn 0.01 O2.
[0053] In some embodiments, the mass ratio of the coating layer in the cathode material is 1% - 5%. For example, this mass ratio can be 1%, 1.5%, 2%, 2.5%, 3%, 3.5%, 4%, 4.5%, 5% or within the range composed of any of the above values; it can be optionally 2% - 4%. In this way, it is beneficial to the improvement of the cycle performance and rate performance of the cathode material.
[0054] In some embodiments, the thickness of the coating layer is less than 10 nm. For example, this thickness can be 0.5 nm, 1 nm, 2 nm, 3 nm, 4 nm, 5 nm, 6 nm, 7 nm, 8 nm, 9 nm or within the range composed of any of the above values. In this way, the thickness of the coating layer is relatively uniform, which is beneficial to the improvement of the chemical stability of the cathode material, as well as its cycle performance and rate performance.
[0055] In some embodiments, the content of phosphorus element in the cathode material is 1500 ppm - 9000 ppm. For example, the content of phosphorus element in the cathode material can be 1500 ppm, 2000 ppm, 3000 ppm, 4000 ppm, 5000 ppm, 6000 ppm, 7000 ppm or within the range composed of any of the above values; it can be optionally 3800 ppm - 5000 ppm. In this way, it is beneficial to the improvement of the cycle performance and rate performance of the cathode material.
[0056] In some embodiments, the layer spacing of the ternary cathode material is 0.47 nm to 0.48 nm. For example, the layer spacing of the ternary cathode material can be 0.47 nm, 0.471 nm, 0.472 nm, 0.473 nm, 0.474 nm, 0.475 nm, 0.476 nm, 0.477 nm, 0.478 nm, 0.479 nm, 0.48 nm or within the range composed of any of the above values. Thus, it helps the insertion and extraction of lithium ions in the material, and then is beneficial to improving the rate performance of the material.
[0057] In a second aspect, the present application provides a method for preparing a cathode material, which can be used to prepare the cathode material of the first aspect of the present application, and may include the following steps:
[0058] Step S10: Add a second solution containing a source of dihydrogen phosphate to a first solution containing a ternary cathode material matrix and a manganese source, and prepare a precursor for coating after the reaction;
[0059] Step S20: Perform a calcination treatment on the precursor for coating to prepare the cathode material. The cathode material includes a core and a coating layer covering at least part of the surface of the core. The core contains a ternary cathode material, and the ternary cathode material satisfies the chemical formula LiNi x Co y Mn 1-x-y O2, 0.6 ≤ x < 1, 0 < y ≤ 0.1, and the coating layer contains manganese phosphate.
[0060] The present application uses a coprecipitation method to prepare the cathode material. In step S10, the manganese source can react with the source of dihydrogen phosphate, and the reaction product is in-situ coated on the surface of the ternary cathode material matrix, so that it is easy to obtain a uniform coating layer; after the calcination treatment of the pre-coating in step S20, the coating product coated on the surface of the ternary cathode material matrix can be decomposed to generate manganese phosphate, so that a uniform coating layer containing manganese phosphate can be obtained.
[0061] Compared with the method of directly grinding and mixing manganese phosphate and the ternary cathode material matrix and then performing calcination to form a coating layer, the coprecipitation method of the present application can achieve in-situ coating of manganese phosphate. This coating method can greatly improve the uniformity of the coating layer, and then is beneficial to the improvement of the chemical stability of the cathode material, as well as the improvement of its cycling performance and rate performance. In addition, the coprecipitation method incorporates a water washing process, and during the formation of the coating layer, it can also consume free lithium compounds (such as Li2CO3 and LiOH) on the surface of the ternary cathode material matrix, reduce the adverse effects of the free lithium compounds on the material, and further improve the cycling performance of the cathode material.
[0062] In some embodiments, in the first solution, the mass ratio of the manganese source to the ternary cathode material matrix is (1.5-5): 100. For example, the mass ratio may be 1.5: 100, 2: 100, 2.5: 100, 3: 100, 3.5: 100, 4: 100, 4.5: 100, 5: 100 or within the range of any of the above values.
[0063] In some embodiments, in the first solution, the mass ratio of the ternary cathode material matrix to the solvent is (0.1-3): 1. For example, the mass ratio may be 0.1: 1, 0.5: 1, 1: 1, 1.3: 1, 1.6: 1, 1.9: 1, 2.3: 1, 2.6: 1, 2.9: 1, 3: 1 or within the range of any of the above values.
[0064] In some embodiments, the mass ratio of the dihydrogen phosphate source to the manganese source is (45-50): 100. For example, the mass ratio can be 45:100, 46:100, 47:100, 48:100, 49:100, 50:100 or within the range of any of the above values.
[0065] In some embodiments, in the second solution, the mass ratio of the dihydrogen phosphate source to the solvent is (0.077~0.385):1.
[0066] In some embodiments, the solvent in the first solution and the solvent in the second solution each independently comprise deionized water.
[0067] In some embodiments, the manganese source includes one or more of manganese sulfate, manganese acetate, and manganese chloride.
[0068] In some embodiments, the dihydrogen phosphate source includes one or more of ammonium dihydrogen phosphate, sodium dihydrogen phosphate, lithium dihydrogen phosphate and potassium dihydrogen phosphate. The dihydrogen phosphate in the dihydrogen phosphate source is weakly acidic, which can regulate the pH in the coprecipitation coating process, promote the formation of the reaction product and the coating process.
[0069] In some embodiments, adding a second solution containing a dihydrogen phosphate source to a first solution containing a ternary cathode material matrix and a manganese source may include:
[0070] The second solution is added dropwise to the first solution under stirring.
[0071] In some embodiments, the dripping rate is 2.5 mL / h to 10 mL / h. Controlling the dripping rate allows the second solution to be added to the first solution more slowly, which is beneficial to improving the uniformity of the formed coating layer, and then to improving the chemical stability of the positive electrode material, as well as improving its cycle performance and rate performance.
[0072] In some embodiments, after step S10 and before step S20, the following step may be further included: drying the coating precursor.
[0073] In some embodiments, the temperature of the drying process is 60° C. to 150° C., and the time of the drying process is 1.5 h to 24 h.
[0074] In some embodiments, the calcination temperature is 250°C to 350°C.
[0075] In some embodiments, the calcination time is 5 h to 6 h.
[0076] In some embodiments, the calcination treatment atmosphere includes an oxygen atmosphere and / or an air atmosphere.
[0077] In a third aspect, the present application provides a positive electrode sheet, comprising the positive electrode material of the first aspect of the present application or the positive electrode material prepared by the preparation method of the second aspect of the present application.
[0078] In a fourth aspect, the present application provides a lithium-ion battery, comprising the positive electrode sheet of the third aspect of the present application.
[0079] In some embodiments, the lithium-ion battery further includes a negative electrode sheet, an electrolyte, and a separator. During the battery charge and discharge process, lithium ions are inserted and removed back and forth between the positive electrode sheet and the negative electrode sheet. The electrolyte plays the role of conducting ions between the positive electrode sheet and the negative electrode sheet. The separator is arranged between the positive electrode sheet and the negative electrode sheet, mainly to prevent the positive and negative electrodes from short-circuiting, while allowing ions to pass through.
[0080] In a fifth aspect, the present application provides an electrical device, comprising the lithium-ion battery of the third aspect of the present application.
[0081] In some embodiments, the type of the electric device is not particularly limited, and it can be any electronic device known in the prior art. For example, the electric device can include, but is not limited to, power tools, electric cars, laptop computers, pen-type computers, mobile computers, e-book players, portable phones, portable fax machines, portable copiers, portable printers, etc.
[0082] Example
[0083] The following are specific examples, which more specifically describe the contents disclosed in this application, and these examples are only for illustrative purposes, because it is obvious to those skilled in the art that various modifications and variations are made within the scope of the disclosure of this application. Unless otherwise stated, all parts, percentages, and ratios reported in the following examples are based on weight, and all reagents used in the examples are commercially available or synthesized according to conventional methods and can be used directly without further processing, and the instruments used in the examples are commercially available.
[0084] Example 1
[0085] 1) Use an electronic balance to accurately weigh 1.63 g of manganese acetate tetrahydrate (Mn(Ac) 2.4 H2O) powder, 100g NCM (LiNi 0.96 Co 0.03 Mn 0.01 O2) powder sample (referred to as NCM-1) was dispersed in 50g of deionized water and stirred at low speed for 1min to obtain the first solution. 0.77g of diammonium phosphate powder was dissolved in 10g of deionized water solution and stirred at low speed for 5min to obtain the second solution. The second solution was slowly added dropwise to the first solution for 4h. The mixed solution was centrifuged and vacuum dried at 60℃ for 24h to obtain the coated precursor, which was referred to as NCM-Pre-1.
[0086] 2) The obtained coating precursor was calcined at 300° C. for 5 h in an air atmosphere to obtain a positive electrode material containing a manganese phosphate coating layer.
[0087] Example 2
[0088] The preparation method is similar to that of Example 1, except that in step 1), manganese acetate tetrahydrate (Mn(Ac) 2.4 The mass of the H2O) powder is 3.26 g, and the mass of the diammonium phosphate powder is 1.54 g, so that the mass proportion of the coating layer in the positive electrode material is 2%.
[0089] Example 3
[0090] The preparation method is similar to that of Example 1, except that in step 1), manganese acetate tetrahydrate (Mn(Ac) 2.4 The mass of the H2O) powder is 4.89 g, and the mass of the diammonium phosphate powder is 2.31 g, so that the mass proportion of the coating layer in the positive electrode material is 3%.
[0091] Example 4
[0092] The preparation method is similar to that of Example 1, except that in step 1), manganese acetate tetrahydrate (Mn(Ac) 2.4The mass of the H2O) powder is 6.52g, and the mass of the diammonium phosphate powder is 3.08g, so that the mass proportion of the coating layer in the positive electrode material is 4%.
[0093] Example 5
[0094] The preparation method is similar to that of Example 1, except that in step 1), manganese acetate tetrahydrate (Mn(Ac) 2.4 The mass of the H2O) powder is 8.15g, and the mass of the diammonium phosphate powder is 3.85g, so that the mass proportion of the coating layer in the positive electrode material is 5%.
[0095] Example 6
[0096] The preparation method is similar to that of Example 1, with the main difference being that in step 1), the dropping time is 1 h.
[0097] Comparative Example 1
[0098] 1) Accurately weigh 100g NCM (LiNi 0.96 Co 0.03 Mn 0.01 O2) powder sample (denoted as NCM-0) was dispersed in 50g of deionized water and stirred at low speed for 1min to obtain the first solution. 10mL of deionized water was slowly added to the first solution for 4h. The mixed solution was centrifuged and dried under vacuum at 60℃ for 24h to obtain the coated precursor.
[0099] 2) The obtained coated precursor was calcined at 300° C. for 5 h in an air atmosphere to obtain a positive electrode material.
[0100] Comparative Example 2
[0101] The preparation method is similar to that of Example 1, except that step 1 is omitted, 1.2 g of manganese phosphate is directly mixed with 100 g of NCM (LiNi 0.96 Co 0.03 Mn 0.01 O2) powder is ground and mixed evenly to obtain a coating precursor.
[0102] Comparative Example 3
[0103] The preparation method is similar to that of Example 1, with the main difference being that in step 1), an equal mass of niobium acetate is used instead of manganese acetate tetrahydrate to obtain a positive electrode material containing a niobium phosphate coating layer.
[0104] Comparative Example 4
[0105] The preparation method is similar to that of Example 1, with the main difference being that in step 1), an equal mass of aluminum sulfate is used instead of manganese acetate tetrahydrate to obtain a positive electrode material containing an aluminum phosphate coating layer.
[0106] The positive electrode materials prepared in Examples 1 to 6 and Comparative Examples 1 to 4 or the lithium ion batteries further prepared therefrom were subjected to relevant performance tests, and the test results are shown in Tables 1 to 3 below.
[0107] Among them, the test conditions or test standards for each performance test item are as follows:
[0108] (1) Mass proportion of the coating layer: Inductively coupled plasma spectroscopy (ICP) and energy spectrum scanning (EDS-mapping) analysis were used to measure the elemental composition and element content contained in the material.
[0109] (2) Structural characterization: X-ray diffractometer (XRD) is used to characterize the material structure. The material interlayer spacing can be calculated using the Bragg equation nλ=2dsinθ, where n is the diffraction order, λ is the X-ray wavelength, d is the crystal plane spacing, and θ is the diffraction angle.
[0110] (3) Morphology test: The sample morphology was observed using scanning electron microscopy (SEM) and transmission electron microscopy (TEM).
[0111] (4) Electrochemical performance
[0112] The positive electrode material is assembled into a CR2032 button cell, wherein the positive electrode sheet is prepared from the positive electrode material, acetylene black and a binder PVDF in a mass ratio of 90:6:4.
[0113] The CR2032 button cell was charged and discharged for the first time at 0.2C in the voltage range of 2.30V~4.25V at room temperature 25℃ to obtain the first discharge specific capacity and the first coulombic efficiency. The button cell was then tested at room temperature 25℃ in the voltage range of 2.30V~4.25V at rates of 0.1C, 1C, and 2C.
[0114] Then, in a high temperature environment of 45°C, charge and discharge were cycled for 100 weeks at 0.3C in the voltage range of 2.30V to 4.25V, and the discharge specific capacity at the 50th week was recorded to obtain the capacity retention rate;
[0115] Capacity retention rate = (50-cycle discharge specific capacity / first discharge specific capacity) × 100%.
[0116] Table 1
[0117]
[0118] Table 2
[0119]
[0120] Table 3
[0121]
[0122] It can be seen from Table 1 above that as the mass proportion of the coating layer containing manganese phosphate increases, the Mn and P contents in the material gradually increase, and the Ni and Co contents gradually decrease. Comparing Table 1 and Table 2 (which are the surface element content distributions of the positive electrode materials of Comparative Example 1 and Example 3, which correspond to the content distributions of each element in the mapping diagram of FIG1 ), it can be seen that there is a difference between the proportions of the overall positive electrode material and the surface elements. The surface Mn element content increases after coating, indicating that the coating is successful.
[0123] It can be seen from Table 3 that after manganese phosphate coating, the 50-week high-temperature cycle performance is greatly improved, among which the cycle performance of Example 3 is relatively better. This is due to the fact that the manganese phosphate-containing coating layer can isolate NCM and electrolyte, improve interface stability, inhibit its side reactions, and stabilize the crystal structure of the layered multi-element material.
[0124] As can be seen from Figure 1, the Ni, Co, and Mn elements are evenly distributed in the uncoated comparative example 1; the Ni, Co, and Mn elements are evenly distributed in the coated example 3, and the Mn content in the sample surface (i.e., the area surrounded by a thickness of 0.5μm to 5μm from the outer surface of the sample to the center of the sample) is greatly increased.
[0125] In Figures 2 to 7, it can be seen through the 20.0K SEM that as the mass percentage of the coating layer increases, the sample surface gradually becomes rough from smooth. When the mass percentage reaches 4%, amorphous manganese phosphate appears on the sample surface. Further magnification through TEM shows that the interior of Comparative Example 1 (Figure 7 (a)) is uniform, while Example 3 (Figure 7 (b)) has a coating layer of about 5nm, as marked by the red dotted line; all of the above prove that the sample coating is successful.
[0126] As can be seen from Figures 8 to 10, for the crystal structure of the NCM powder sample, coated precursor, and positive electrode material of Example 4, manganese phosphate coating will cause the (003) peak to shift to a low angle by about 0.05°, that is, the (003) crystal plane interlayer spacing increases. The increase in interlayer spacing helps lithium ions to be deintercalated in the material and improves the rate performance of the material. On this basis, the present application conducted rate performance tests on Comparative Examples 1 to 4 and Examples 1 to 6, as shown in Table 3. As the mass proportion of the coating layer increases, the capacity of the sample at 0.1C decreases, while the capacity at 2.0C increases, confirming that manganese phosphate coating improves the rate performance of the sample, and when the mass proportion of the coating layer is 1% to 4%, the rate performance at 2.0C is higher. Compared with Comparative Example 2, the high temperature cycle performance of Example 1 is greatly improved, which may be the reason why Example 1 uses a coprecipitation method to reduce residual lithium on the surface of the material. Compared with Comparative Examples 3 and 4, Example 1 has higher rate performance and better high temperature cycle stability. In addition, manganese sources have lower prices than niobium sources and aluminum sources, so manganese phosphate coating has better industrial prospects.
[0127] The above results show that the rate performance and high-temperature cycle performance of the positive electrode material coated with manganese phosphate by the co-precipitation method are greatly improved.
[0128] The technical features of the above-described embodiments may be arbitrarily combined. To make the description concise, not all possible combinations of the technical features in the above-described embodiments are described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification.
[0129] The above-mentioned embodiments only express several implementation methods of the present application, and the descriptions thereof are relatively specific and detailed, but they cannot be understood as limiting the scope of the invention patent. It should be pointed out that, for a person of ordinary skill in the art, several variations and improvements can be made without departing from the concept of the present application, and these all belong to the protection scope of the present application. Therefore, the protection scope of the patent of the present application shall be subject to the attached claims.
Claims
1. A positive electrode material, It is characterized in that include: A core and a coating layer covering at least a part of the surface of the core, the core contains a ternary cathode material, and the ternary cathode material satisfies the chemical formula LiNi x Co y Mn 1-x-y O 2 , 0.6 ≤ x < 1, 0 < y ≤ 0.1, and the coating layer contains manganese phosphate.
2. The positive electrode material according to claim 1, It is characterized in that Meet one or more of the following conditions: (1) The mass proportion of the coating layer in the positive electrode material is 1% to 5%, and can be 2% to 4%; (2) The thickness of the coating layer is less than 10 nm; (3) The phosphorus content in the positive electrode material is 1500ppm~9000ppm, and can be optionally 3800ppm~5000ppm.
3. The positive electrode material according to claim 1 or 2, It is characterized in that The interlayer spacing of the ternary positive electrode material is 0.47nm~0.48nm.
4. A method for preparing a positive electrode material, It is characterized in that include: Adding a second solution containing a dihydrogen phosphate source to a first solution containing a ternary cathode material matrix and a manganese source, and preparing a coating precursor after reaction; The coated precursor is calcined to prepare the positive electrode material. The positive electrode material includes a core and a coating layer covering at least a part of the surface of the core. The core contains a ternary positive electrode material, and the ternary positive electrode material satisfies the chemical formula LiNi x Co y Mn 1-x-y O 2 , where 0.6 ≤ x < 1, 0 < y ≤ 0.1, and the coating layer contains manganese phosphate.
5. The preparation method according to claim 4, It is characterized in that Meet one or more of the following conditions: (1) In the first solution, the mass ratio of the manganese source to the ternary cathode material matrix is (1.5-5):100; (2) In the first solution, the mass ratio of the ternary cathode material matrix to the solvent is (0.1-3):1; (3) The mass ratio of the dihydrogen phosphate source to the manganese source is (45-50):100; (4) In the second solution, the mass ratio of the dihydrogen phosphate source to the solvent is (0.077-0.385):1; (5) The manganese source includes one or more of manganese sulfate, manganese acetate and manganese chloride; (6) The dihydrogen phosphate source includes one or more of ammonium dihydrogen phosphate, sodium dihydrogen phosphate, lithium dihydrogen phosphate and potassium dihydrogen phosphate.
6. The positive electrode material according to claim 4 or 5, It is characterized in that Adding a second solution containing a dihydrogen phosphate source to a first solution containing a ternary cathode material matrix and a manganese source comprises: Under stirring, adding the second solution dropwise to the first solution; Optionally, the dripping rate is 2.5 mL / h~10 mL / h.
7. The preparation method according to claim 4 or 5, It is characterized in that Meet one or more of the following conditions: (1) The calcination temperature is 250°C to 350°C; (2) The calcination time is 5h~6h; (3) The calcination treatment atmosphere includes an oxygen atmosphere and / or an air atmosphere.
8. A positive electrode sheet, It is characterized in that The positive electrode material comprises the positive electrode material according to any one of claims 1 to 3 or the positive electrode material prepared by the preparation method according to any one of claims 4 to 7.
9. A lithium ion battery, It is characterized in that Including the positive electrode sheet as claimed in claim 8.
10. An electrical device, It is characterized in that Includes the lithium ion battery as claimed in claim 9.
